Relevance of Brain 18F-FDG PET Imaging in Probable Seronegative Encephalitis With Catatonia: A Case Report - Guetta, Michaël; Kas, Aurélie; Aouidad, Aveline; Soret, Marine; Allenbach, Yves; Bordonné, Manon; Oppetit, Alice; Raffin, Marie; Psimaras, Dimitri; Cohen, David; Consoli, Angèle (Frontiers in Psychiatry, 2021)
Autoimmune encephalitis (AIE) is a rare, severe and rapidly progressive encephalopathy, and its diagnosis is challenging, especially in adolescent populations when the presentation is mainly psychiatric. Currently, cerebral 18-fluorodeoxyglucose positron emission tomography (¹⁸F-FDG-PET) imaging is not included in the diagnosis algorithm. We describe a 16-year-old patient with probable seronegative encephalitis with catatonia for which several cerebral PET scans were relevant and helpful for diagnosis, treatment decision making, and follow-up monitoring. The patient recovered after two years of treatment with etiologic treatment of AIE and symptomatic treatment of catatonia. This case suggests a more systematic assessment of the clinical relevance of ¹⁸F-FDG-PET imaging in probable seronegative AIE.